2019
DOI: 10.1039/c8nr09356c
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the sodium ion storage mechanism of gallium sulfide (Ga2S3): a combined experimental and theoretical approach

Abstract: Developing sodium ion battery (SIB) anode materials of a low-cost and high-capacity nature for future large-scale applications still involves challenges.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 41 publications
0
17
0
Order By: Relevance
“…This reaction mechanism including rst intercalation, conversion reaction and alloy process are similar to previous reports in Ga 2 O 3 , Ga 2 S 3 , CoGa 2 S 4 and NiGa 2 O 4 , etc. 14,19,21,36 Fig . 3b shows the galvanotactic discharge-charge (GDC) prole for the rst three cycles at a current density of 0.5 A g À1 , in which the GaOOH electrode shows a discharging capacity of 1343 mA h g À1 and charging capacity of 602 mA h g À1 upon the initial cycle, with coulombic efficiency of 45%.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This reaction mechanism including rst intercalation, conversion reaction and alloy process are similar to previous reports in Ga 2 O 3 , Ga 2 S 3 , CoGa 2 S 4 and NiGa 2 O 4 , etc. 14,19,21,36 Fig . 3b shows the galvanotactic discharge-charge (GDC) prole for the rst three cycles at a current density of 0.5 A g À1 , in which the GaOOH electrode shows a discharging capacity of 1343 mA h g À1 and charging capacity of 602 mA h g À1 upon the initial cycle, with coulombic efficiency of 45%.…”
Section: Resultsmentioning
confidence: 99%
“…18 Therefore, Ga-based materials including Ga 2 O 3 , Ga 2 S 3 , Ga 2 Se 3 , etc, have attracted interest as LIBs anodes. [19][20][21] Furthermore, oxyhydroxide has been employed as material for LIBs or supercapacitors, 22,23 because of their ultrafast and reversible surface redox reactions between OOH-group and transition metal ions for capacitive charge storage. In this regards, gallium oxyhydroxide (GaOOH) with theoretical capacity of $1304 mA h g À1 is also expected to show good performance due to both Ga existence and capacitive behavior from OOH group.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, the controllable preparation of Ga 2 S 3 nanostructures remains a challenge. Up to now, the synthesis mainly focuses on the template-assited method followed by a thermal treatment [64,129,[131][132][133]. Hiring metal-organic frameworks (MOFs, MIL-96) as template precursor accompanied by a sulfuration process, Wang et al obtained dodecahedral Ga 2 S 3 /C structures, as is shown in Fig.…”
Section: Gallium Sulfide Anodesmentioning
confidence: 99%
“…Though the voltage window was narrower, it still had a utilization of 385 mA h g À1 at 100 mA g À1 after 200 cycles. Apart from Ga-MOFs, GaOOH is also an ideal template for the synthesis of Ga 2 S 3 [64]. As is shown in Fig.…”
Section: Gallium Sulfide Anodesmentioning
confidence: 99%
See 1 more Smart Citation